Appropriateness of diagnostic effort in hospital emergency room attention for episodes of COPD exacerbation. Issue 5 (2nd July 2015) - Rivas‐Ruiz, Francisco; Redondo, Maximino; González, Nerea; Vidal, Silvia; García, Susana; Lafuente, Iratxe; Bare, Marisa; Cano Aguirre, María del Puerto; Quintana‐López, José María; Grupo IRYSS‐COPD; Martínez‐Tapias, Jesús; Ruiz, Alba; et al.
Abstract Rationale, aims and objectives To assess the adequacy of diagnostic effort in the emergency departments of Spanish hospitals with respect to episodes of exacerbation of chronic obstructive pulmonary disease (COPD). Methods A descriptive cross‐sectional study, conducted between 2007 and 2010 in 15 hospitals in Andalusia, Catalonia, Madrid and the Basque Country. The study population included cases of COPD exacerbation attended at the emergency departments of the participating hospitals. Diagnostic efforts were considered sufficient and appropriate when the emergency room conducted a clinical evaluation including electrocardiogram, chest X‐ray, arterial blood gas analysis and spirometry. Results 2852 episodes of COPD exacerbation attended in hospital emergency departments were assessed. 91.4% of the patients were male, with a mean age of 72.8 (SD 9.5) years, and 45.6% had had a previous emergency admission. The diagnostic effort was considered adequate in 60.1% of the episodes (95% CI: 58.3–61.9). The inter‐hospital range of variation25–75 was 1.67 and the coefficient of variation was 28.3%. In multivariate analysis, adjusting for hospital, date of admission and previous hospitalization, among the male patients, the OR for adequate diagnostic effort was 1.38 (95% CI: 1.04–1.84) Conclusion With respect to diagnostic effort, inequities were observed in our assessment of episodes of COPD exacerbation attended in the emergency departments of Spanish public hospitals. In a high percentage of cases (40%), proper assessment was not conducted. Moreover, inter‐individual and inter‐hospital differences were observed.